New perspectives for the drawings of the Italian architecture archives: reflections and experiments (diségno, 2022)
The value of Italian architecture is linked not only to the built work, but also to the apparatus of its representations, a complex world of information often scattered in different places of conservation and treated in a non-homogeneous way. The paper aims to present some reflections on the contributions that the discipline of drawing can provide in the different areas –knowledge, preservation, use and accessibility– of architectural drawing conservation and enhancement process. The research highlights the need for a unitary conceptual model of management that includes: the descriptive data, through a uniform path of cataloguing; the realisation of digital analysis and reconstructions, through methodologies that allow the evaluation and visualisation of their degree of reliability; the definition of strategies and products to implement different forms of accessibility according to the type of recipient and interaction desired.
Keywords: drawings archive; 3D modelling; virtual reality; augmented reality; accessibility